The Phenomenon of al-Hazf in the Qur'an: An Analysis of the Rasm Rule in Surah Ali-Imran - Djola, Fakhrun; Laila, Nur; Raharja, Hatta; Fitri Juwita, Salma (ELOQUENCE : Journal of Foreign Language, 2022)
Background: al-Hadzf is one of the very interesting Rasm rules studied, because it deals with the elimination of letters or lafaz that will not damage the meaning of a sentence, but has linguistic reasons that make it more unique, interesting, and has an i'jaz. Purpose: This study aims to find out the phenomenon of al-Hadzf letters and words in the Quran, in surah Ali-Imran. Method: The method used in this study is descriptive qualitative through a phenomenological approach to language by looking at the phenomenon of letter elimination, classifying, and analyzing based on its rules. Results and Discussion: The results of this study show that there are 33 types of words in the Surah Ali Imran which are included in the rules of al-Hadzf. In addition to being dominated by singular nouns and verbs, there is also a demonstrative noun. Conclusions and Implications: From the discussion above, the author concludes that there are 33 words that experience hadzf in surah ali Imran. The 33 words are dominated by hadzf Alif, and occur in mufrad, mutsanna, and plural isim. In the form of fi'il as well, al-Hadzf is found in madhi and mudhari fi'il with word scales (فاعل - يفاعل) (تفاعل - يتفاعل). If we look at the existence of various mushaf in Indonesia, this hadzf rule is the same and different, some are consistent with hadz and some are istbat, or a mixture of both. This research has implications for the knowledge of the rules of writing Arabic orthography studied in imla' and Rasm sciences. The rule makes it clear that there is a phenomenon of letters being read but not written, some being written but not being read, and having a unique meaning.